2022
DOI: 10.1002/aelm.202200279
|View full text |Cite
|
Sign up to set email alerts
|

High β‐phase Poly(vinylidene fluoride) Using a Thermally Decomposable Molecular Splint

Abstract: of large-area thin-film, micro-patterning, low-temperature process, and flexibility. [7,8] Ferroelectric polymers such as polyvinylidene fluoride (PVDF) have been investigated as alternatives to their inorganic counterparts. It is known that C-F dipoles in PVDF align parallel to the external electric field, and remanent polarization remains after removing the field, which leads to piezoelectricity and pyroelectricity in PVDF. Depending on preparation methods, PVDF exhibited several different crystalline phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…According to the literature, the typical IR spectrum of semi crystalline PVDF contains peaks at 763, 795, 975, and 1384 cm − ¹ for 𝛼 phase (TGTG conformation) and 839, 1275, and 1402 cm − ¹ for 𝛽 phase PVDF (TTTT conformation). [36][37][38][39][40][41] In Figure 2a,b, the IR spectra of the films coated at 1000 rpm show characteristic to 𝛼 phase peak at 763 cm − ¹ corresponding to CF 2 bending and skeletal bending along with peak at 839 cm − ¹ for CH 2 rocking corresponding to 𝛽 phase and by a convention these peaks are used for evaluation of the 𝛽 phase composition of PVDF. [36][37][38][39][40][41] As the coating speed was increased to 2000 rpm the intensity of the peak at 763 cm − ¹ reduced relative to the absorbance peak at 839 cm − ¹ indicating occurrence of 𝛼 to 𝛽 phase transformation.…”
Section: Characterization Of Phase Composition Of Pvdf Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, the typical IR spectrum of semi crystalline PVDF contains peaks at 763, 795, 975, and 1384 cm − ¹ for 𝛼 phase (TGTG conformation) and 839, 1275, and 1402 cm − ¹ for 𝛽 phase PVDF (TTTT conformation). [36][37][38][39][40][41] In Figure 2a,b, the IR spectra of the films coated at 1000 rpm show characteristic to 𝛼 phase peak at 763 cm − ¹ corresponding to CF 2 bending and skeletal bending along with peak at 839 cm − ¹ for CH 2 rocking corresponding to 𝛽 phase and by a convention these peaks are used for evaluation of the 𝛽 phase composition of PVDF. [36][37][38][39][40][41] As the coating speed was increased to 2000 rpm the intensity of the peak at 763 cm − ¹ reduced relative to the absorbance peak at 839 cm − ¹ indicating occurrence of 𝛼 to 𝛽 phase transformation.…”
Section: Characterization Of Phase Composition Of Pvdf Filmsmentioning
confidence: 99%
“…The equations below were used for quantitative estimation of the 𝛽 phase content of the PVDF films. [40] A 𝛼 = − logT 𝛼 (1)…”
Section: Characterization Of Phase Composition Of Pvdf Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scientists have developed a number of processing techniques to either directly extract the ⊎-phase from the melt or transform the ⊍-phase into a desirable structure. [12][13][14][15][16] Several studies have demonstrated that high temperatures, very high pressures or highly rapid cooling rates are necessary to produce the ⊎-phase from the melt directly. This is because PVDF is a highly crystalline material that solidifies rapidly during cooling, leading to the formation of the less desirable ⊍-phase, which has inferior ferroelectric and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scientists have developed a number of processing techniques to either directly extract the β ‐phase from the melt or transform the α ‐phase into a desirable structure 12–16 . Several studies have demonstrated that high temperatures, very high pressures or highly rapid cooling rates are necessary to produce the β ‐phase from the melt directly.…”
Section: Introductionmentioning
confidence: 99%